Investigation on prevalence, risk factors, and genetic diversity of Pediculus humanus capitis among primary school children - AL-Daoody, Ahmed Akil Khudhair; Mohammed, Asmaa Khalis; Jabbary, Hawri Hawar Mohammed; Ali, Fattma A.; Ibrahim, Hanifa Abdulkareem; Abdullah, Kawther Muhsin; Mawlud, Sara Ismail; Rahman, Sara Jubrael (Cellular and Molecular Biology, 2022)
Pediculosis is an integumentary disease caused by the ecto-parasite Pediculus humanus capitis, which infests human hair. It is a common public health problem that is most prominent worldwide in elementary school children. The current study aimed to investigate the prevalence, risk factors, and genetic diversity of P. humanus capitis among primary school children in the Erbil province. For this purpose, this study was conducted from October 2019 to December 2019 among 1100 randomly selected elementary school children aged 6-12. Data collection was performed via a regular questionnaire and physical hair examination. For the genetic diversity part, after collecting one louse randomly from each individual, DNA was extracted. The mitochondrial Cox1 gene was then amplified by universal primer and PCR. Gene sequencing was performed by ABI (BioNEER, South Korea). Data analysis was done by Chi-Square and T-test using the SPSS ver. 23. The overall infestation rate was 21.27%, and the rate was significantly higher among females (34.93%) compared to males (7.91%). Some variables had found the prevalence rate to be strongly affected. This included age; the rate was not significant (26.87%) in the age group 8-9 years compared to other age groups. According to hair length, the rate was significantly increased (36.52%) among children with tall hair. In terms of hair type, the incidence of curly-haired children was significantly higher (31.54%); in terms of hair color, there were not significant differences among blonde children (25.90%) and others. According to the results of Cox1 gene sequencing, of 234 infested children to lice, 86 (36.75%) of them were exposed to clade A, 38 (16.24%) were exposed to clade B, clade C has not been seen among any children (0%), 105 students (44.87%) were exposed to clade D, and 5 of them exposed to clade E (2.14%). Eventually, a significantly higher incidence (33.78%) was reported in rural primary school children. The infection rate of human head lice in Erbil province is still high, which is one of the health problems of children in public schools.